The effects of organic amendments and shade levels on the growth performance of aloe vera plants: Aloe Vera Growth under Shade and Amendments (Journal of the Sylhet Agricultural University, 2025)
A field study was conducted at Sylhet Agricultural University, Sylhet, during the summer season from April to June 2019. The objective of the study was to assess the impact of organic amendments and shadow levels by changing light exposure on the growth contributing features of the aloe vera plant. The experiment was designed according to a factorial experiment in a Randomized Complete Block Design (RCBD) with various organic amendments and two levels of shadow. Organic amendments were cow dung, vermicompost, and Trichocompost. Two distinct degrees of light exposure were used in the experiment viz., complete shade (4×100 lux) and partial shade (125×100 lux). The growth performance of the plants was significantly affected by organic inputs as well as varying levels of shade. The maximum plant height (15.37 cm) and number of leaves (18.00) were bserved at110 days after transplanting (DAT) in the pots where Trichocompost semi-shed environment was employed. But the highest number of stems (10.47) was recorded at 110 days after transplanting (DAT) when combination of Trichocompost and complete shade were applied. The findings of the current study can be advisable to utilize Trichocompost as a growth medium for aloe vera cultivation in partially shaded environments in order to achieve optimal growth.J. Sylhet Agril. Univ. 11(2): 75-80, 2024